Organizational Climate in Commercial Banks of Nepal (Management Dynamics, 2024)
Organizational climate is defined as the perception of employees toward the existing working environment, policies, and strategies of the organization. According to the environmental person fit theory, the social environment influences the attitude and behavior of the employees, so the management of the organization should manage the attitude and behavior of employees by bringing change in their existing policies and strategies related to organizational climate. The objective of this study was to identify the organizational climate level in employees at Nepal Bank Ltd. For that purpose, 157 structured questionnaires were distributed to the employees of the central office and banking office of the bank. Only 114 employees had given their opinion, and then it was analyzed with the help of mean, standard deviation, correlation, ANOVA, and regression. The analysis has shown that employees are at an agreeable level in eight items of organizational climate, except in financial benefits. The age and tenure have positive relationships with organizational climate at the nominal level, with negligible impact. Age has no impact on organizational climate according to the R2 analysis. The management of the bank should make an effort to maintain at least the present level of perception and should try to improve the existing level. The management should improve the organizational climate perception of employees by regularly studying changes in attitude and behavior of employees at work. The grievance on financial benefits should be managed by sharing it with the employees.